Circulating IL-6 and not its circulating signaling components sIL-6R and sgp130 demonstrate clinical significance in NSCLC patients treated with immune checkpoint inhibitors - Nakahara, Yoshiro; Kouro, Taku; Motoyama, Satoru; Miura, Masatomo; Fujita, Kazuma; Igarashi, Yuka; Higashijima, Naoko; Matsuo, Norikazu; Himuro, Hidetomo; Wei, Feifei; Horaguchi, Shun; Tsuji, Kayoko; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Clinical roles of plasma IL-6 levels have been reported in patients with various cancers, including non-small cell lung cancer (NSCLC), treated with immune checkpoint inhibitors (ICIs). However, the roles of other IL-6 signaling components, soluble IL-6 receptor (sIL-6R) and soluble gp130 (sgp130), in the plasma have not been elucidated.Methods: Blood was collected from 106 patients with NSCLC before initiation of ICI treatment (anti-PD-1 or anti-PD-L1 antibody). Plasma levels of IL-6, sIL-6R, sgp130, and their complexes were assessed by Cox regression hazard model to evaluate their clinical significance. The clinical role of IL-6 or IL-6R genetic polymorphisms was also analyzed.Results: Cox regression analysis showed that higher plasma IL-6 levels significantly predicted unfavorable overall survival (OS; hazard ratio [HR] 1.34, 95% confidence interval [CI] 1.05 -1.68, P = 0.012) in NSCLC patients treated with ICIs. However, plasma sIL-6R and sgp130 levels showed no prognostic significance (P = 0.882 and P = 0.934, respectively). In addition, the estimated concentrations of binary IL-6:sIL-6R and ternary IL-6:sIL-6R:sgp130 complexes and their ratios (binary/ternary complex) were not significantly associated with OS (P = 0.647, P = 0.727, and P = 0.273, respectively). Furthermore, the genetic polymorphisms of IL-6 (-634G>C) and IL-6R (48892A>C) showed no clinical role by Kaplan-Meier survival analysis (P = 0.908 and P = 0.639, respectively).Discussion: These findings demonstrated the clinical significance of plasma levels of IL-6, but not of other IL-6 signaling components, sIL-6R and sgp130, suggesting that classical IL-6 signaling, but not trans-signaling, may be related to anti-tumor immune responses in cancer patients treated with ICIs.